Emergency medical services Milestones 2.0: What has changed?. Issue 6 (8th December 2022) - Nesbit, Chadd E.; Mastenbrook, Joshua D.; Ball, Matthew T.; Rinnert, Kathy J.; Edgar, Laura
Abstract: Background: Since 2015, development of competencies by emergency medical services (EMS) fellows have been evaluated using the EMS Milestones 1.0 developed by a working group consisting of relevant stakeholders convened by the Accreditation Council for Graduate Medical Education (ACGME). Feedback from users and data collected from the milestones assessments in the interim indicated a need for revision of the original milestones. In May 2021, the Milestones 2.0 working group was convened for the purpose of revising this specialty‐specific assessment tool. Methods: A working group consisting of representatives from American Board of Emergency Medicine, the Review Committee for Emergency Medicine, and volunteers selected by the ACGME Milestones Committee, chaired by the ACGME vice president for milestones development, was convened using a virtual platform to revise the milestones and develop a supplemental guide for use along with the Milestones 2.0. There were no in‐person meetings of this working group due to the COVID‐19 pandemic. Results: Data from milestones reporting, discussion within the working group, stakeholder input, and public commentary were used to revise the original milestones. A new supplemental guide to enhance milestone usability and provide recommended resource materials was also developed for use alongside the milestones. Discussion: The EMS Milestones 2.0 and accompanying supplemental guide provide an updated framework for fellowship programs to use as a guide for developing the competencies necessary for independent practice as EMS physicians and in the formal, competency‐based evaluation of trainees as required by the ACGME.